2015
DOI: 10.1002/jat.3267
|View full text |Cite
|
Sign up to set email alerts
|

Structural dependence ofin vitrocytotoxicity, oxidative stress and uptake mechanisms of poly(propylene imine) dendritic nanoparticles

Abstract: The in vitro cytotoxic and intracellular oxidative stress responses to exposure to poly(propylene imine) (PPI) dendritic nanoparticles of increasing generation (number of repeated branching cycles) (G0-G4) were assessed in an immortal noncancerous human keratinocyte cell line (HaCaT). Confocal fluorescence microscopy with organelle staining was used to explore the uptake and intracellular trafficking mechanisms. A generation-and dose-dependent cytotoxic response was observed, increasing according to generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Notably, uptake of the external agent can occur via a number of different mechanisms, which can depend on the agent itself and the cell line used, and the subsequent cellular response can be substantially different. As an example, extending the series of poly (propylene imine) dendrimers to generation 0-2, whereas the higher generations are seen to cause oxidative stress after endocytosis, the lower generations are seen to act as antioxidants, and the lack of evidence of endocytosis suggests a transition from active uptake of the larger higher generation dendrimers, to passive uptake of the smaller, lower generation [49] . Thus, an acellular assessment of the reactivity of an agonist is not sufficient to predict their cellular response [50] .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, uptake of the external agent can occur via a number of different mechanisms, which can depend on the agent itself and the cell line used, and the subsequent cellular response can be substantially different. As an example, extending the series of poly (propylene imine) dendrimers to generation 0-2, whereas the higher generations are seen to cause oxidative stress after endocytosis, the lower generations are seen to act as antioxidants, and the lack of evidence of endocytosis suggests a transition from active uptake of the larger higher generation dendrimers, to passive uptake of the smaller, lower generation [49] . Thus, an acellular assessment of the reactivity of an agonist is not sufficient to predict their cellular response [50] .…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Khalid et al (2015) of cellular uptake of PPI dendrimers have demonstrated that, 488 although the larger generation PPI dendrimers are endocytosed and elicit similar responses to 489 PAMAM equivalents in HaCaT cells, for smaller generation PPI dendrimers, uptake by passive 490 diffusion occurs and, when the dendrimers enter the cell in this way, they were observed to act as 491 antioxidants and elicit a significantly reduced cytotoxic effect. 18 BSO exposure has been shown 492 to permeabilise the cell membrane, 28 and as a result, it is proposed that the PAMAM G4 and G6 493 dendrimers are able to circumvent the endocytotic process, are uptaken by passive diffusion, and, 494…”
mentioning
confidence: 99%
“…Regarding the cytotoxicity of dendrimers, several reports indicate a strong correlation between toxicity and intracellular ROS production [23][24][25]. Increase in ROS is biphasic, with the first phase increase being attributed to the active uptake of the dendrimer (in this case polyamidoamine (PAMAM)) by clathrin-mediated endocytosis [25][26][27]. The second phase is due to mitochondrial injury as PAMAM localizes to these organelles [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in ROS is biphasic, with the first phase increase being attributed to the active uptake of the dendrimer (in this case polyamidoamine (PAMAM)) by clathrin-mediated endocytosis [25][26][27]. The second phase is due to mitochondrial injury as PAMAM localizes to these organelles [25,28]. Cytotoxicity has already been found to be correlated with increased ROS production; for example, for PAMAM and cationic phosphorus dendrimers (CPD) on N2a cells [29], whereas viologen-phosphorus dendrimers (VPD) only slightly decreased the ROS level in mHippoE-18 and N2a cells [30].…”
Section: Discussionmentioning
confidence: 99%